Intravenous immunoglobulin treatment for acute attacks in myelin oligodendrocyte glycoprotein antibody disease - Lotan, Itay; Chen, John J; Hacohen, Yael; Abdel-Mannan, Omar; Mariotto, Sara; Huda, Saif; Gibbons, Emily; Wilf-Yarkoni, Adi; Hellmann, Mark A; Stiebel-Kalish, Hadas; Pittock, Sean J; Flanagan, Eoin P; et al. (Multiple sclerosis, 2023)
The potential therapeutic benefit of intravenous immunoglobulins (IVIGs) for acute attacks of myelin oligodendrocyte glycoprotein antibody disease (MOGAD) is unknown. The objective was to describe the outcomes of IVIG treatment for acute MOGAD attacks. A retrospective observational study involving seven tertiary neuroimmunology centers. Data collection included patients' demographics, Expanded Disability Status Scale (EDSS), and visual acuity (VA) before the attack, at the nadir of the attack before IVIG treatment, and at follow-up visits ⩾3 months after treatment. Thirty-nine patients were included, of which 21 (53.8%) were female. The median age was 23 years (range 5-74 years), and the median disease duration was 4 months (range 0-93 months). The most common type of attack treated with IVIG was isolated optic neuritis (ON) (unilateral = 14, bilateral = 5, associated with transverse myelitis (TM), = 1), followed by acute disseminated encephalomyelitis (ADEM) ( = 8), multifocal ( = 7), TM ( = 3), brainstem ( = 1), and other encephalitis ( = 1). A significant improvement in both the EDSS and VA measures was observed at follow-up compared to the time of IVIG treatment initiation ( < 0.0001 for both outcome measures). IVIG may be an effective treatment option for acute MOGAD attacks. Further prospective studies are warranted to validate our results.